Sterilization of micronized indomethacin - Krupianskaya, Karyna; Croonenborghs, Bart; Gillet, Annick; Appeltans, Bernard; Meyers, Anke; DeMent, Aaron; Van den Mooter, Guy; Van Schepdael, Ann; Haghedooren, Erik (Frontiers in Analytical Science, 2023)
Sterilization is a pivotal topic in the pharmaceutical industry, whereby the nomenclature of “sterile” refers to the absence of viable microorganisms. Since microorganisms can reproduce in the body and cause potentially fatal infections, it is critical to sterilize parenteral products to prevent this. In recent years, 70 to 90 % of potential drugs and 40 % of marketed drugs have demonstrated a low solubility. Micronization is a widely spread approach to increase the dissolution rate. A subset of micronized products require sterilization, but published studies on the effects of sterilization on micronized products are currently lacking. The effect of sterilization on the micronized active pharmaceutical ingredient indomethacin was explored in this study. The sterilization methods in scope were one photon-based method using gamma irradiation and one gas-based method with nitrogen dioxide gas. Indomethacin was micronized using two micronization techniques, cryomilling and spray drying. Different conditions were used for cryomilling where the number of grinding balls in the ball mill and the degree of filling were varied. The solid state of all samples was evaluated after micronization, and only the effectively micronized samples were selected for sterilization with gamma rays and nitrogen dioxide. Gamma irradiation was performed with the active pharmaceutical ingredient stored at -80 °C at a commonly used industry standard target dose of 25 kGy. Nitrogen dioxide sterilization took place at 21 °C, a concentration of 10 mg/L, a relative humidity of 30 % and using two NO2 pulses. Before and after sterilization, all samples were analyzed by high performance liquid chromatography with UV detection, whereby the assay of indomethacin was examined as well as the peak purity and the formation of impurities. In comparison to the non-micronized reference, both sterilization methods demonstrate a significant decrease of content of micronized samples and an increase of the impurity profile. The non-micronized sample showed no significant difference after sterilization. It could thus be observed that micronized indomethacin samples demonstrate more degradation and are subsequently more susceptible to degradation upon sterilization with gamma rays and nitrogen dioxide gas, driving towards the need for assessment of the micronization impact combined with sterilization approach.